Vaginal prolapse in ewes: A critical review of the literature and the disease status in Greece : A critical review of the literature and description of the disease status in Greece - Christodoulopoulos, Giorgos (Journal of the Hellenic Veterinary Medical Society, 2023)
This article is a critical review of the vaginal prolapse in ewes. It describes the pathophysiology, risk factors, clinical signs, treatment, and prevention of the disease. It also describes the epidemiology of the disease in Greece based on data from the Clinic of Medicine (Faculty of Veterinary Science, University of Thessaly). The data show that the disorder is a rare condition in the Greek sheep industry. Finally, the influence of highly elevated feeders and also the influence of injectable chorionic gonadotrophin on the risk of vaginal prolapse are emphasized as significant risk factors for the disease in the modern sheep industry.